Corpo femminile come strumento d’indagine nel romanzo Acciaio di Silvia Avallone - Puto, Małgorzata (Romanica Silesiana)
Body Image as the Way to Express Femminity Acciaio by Silvia Avallone The analyzed text puts a great emphasis on the human as physical beings in a physical world, in which body image is a meaningful and conscious way to express identity. The female identity includes concepts of self-esteem, self-perception, sexuality and social role and it can be challenging for a number of reasons. Body image can be a powerful way to fulfill the social expectations but it can also be very vulnerable because appearances change so much and cultural messages that fuel dissatisfaction can be very strong. Having a beautiful body can easily be linked to the concepts of success, sexuality, great expectations. Having ugly body can lead to emargination and struggling against the world that from the ancient times promotes the value of beauty in female. Key words: body-conscious, identity, evolution, postmodernism.<br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;" />